Nonconvulsive Kainic Acid-Induced Seizures Elicit Age-Dependent Impairment of Memory for the Elevated Plus-Maze - Mikulecká, Anna; Krsek, Pavel; Mares, Pavel (Epilepsy & behavior, 2000)
The goal of this study was to evaluate changes in spatial learning in adult and immature rats during and after nonconvulsive seizures. An elevated plus-maze was used in 18- and 25-day-old and adult rats. Kainic acid (KA 6 mg/kg) was administered 60 minutes before the first exposure (Experiment 1) or after a 3-day pretraining (Experiment 2, only adult rats). Animals were retested three times with 24-hour intervals. EEG activity was monitored in 18-day-old rats. KA prolonged the transfer latency (TL) in all age groups. In the youngest group the TL was prolonged 24 hours after KA when epileptic EEG graphoelements were still registered. In both older groups, prolonged TL was measured only 60 minutes after KA. In the pretrained adults, significantly prolonged TLs persisted for 24 hours after KA. KA changed the performance of adult and immature rats in the elevated plus maze not only during nonconvulsive seizures but also 24 hours later.